Sustainable 3D-Printed food packaging from agricultural waste: A review of materials, properties, and applications - Avchar Sahil Panjabrao; Hamid; Kshirod Kumar Dash; Deepika Kathuria; Rafeeya Shams; Prasad Chavan; Shaikh Ayaz Mukarram; Béla Kovács (Journal of Agriculture and Food Research)
The unique process of making 3D printed food packaging from agricultural waste is one of the most emerging ways of sustainable, biodegradable and eco-friendly packaging. This is happening because of the merging of two technologies, 3D printing and recycling/upcycling of agricultural waste. New useable materials will be created and further utilized for food packaging. The technique involves collecting all agricultural waste and then combining it into printable media with the capacity of extrusion technology from a 3D printer, moulding food packaging products. Flour, cellulose, and lignin in agricultural waste are easily converted to biopolymers that serve as base materials for 3D printing. Generally, such biopolymers are required to blend with additional materials for strength and durability. So, this technology utilizes agricultural waste as an eco-friendly substitute for conventional petroleum-based plastics, ultimately contributing to a significant reduction in the environmental impact caused by food packaging. Processing agricultural waste into printed materials involves extensive processing steps like drying, grinding, and blending. The development of better composite materials from agricultural wastes with better mechanical and barrier properties is an ongoing research area. The reproduction technology is evolving into a faster and more efficient means of printing, making it eventually applicable to extensive food packaging applications. The technology utilizes much available agricultural by-product waste to create more sustainable alternatives to conventional packaging materials while giving elbow room for customizing functional food packaging designs. The study's aim was to analyse the kinds of biopolymers and natural filler types used in the formulation of 3D printing filaments from agro-industrial wastes for food packaging applications. This work investigates the effects of processing methods on the physicochemical parameters of the 3D printed composites used in food packaging.